Health matters: the social impacts of street-involved youth's participation in a structured leisure programme. Issue 1 (2nd January 2016) - McClelland, Carolyn; Giles, Audrey R.
Abstract : In this ethnographically informed study, we used a Foucauldian approach to examine the social impacts of street-involved youth's participation in a structured leisure programme. Our findings suggest that structured leisure activities help to facilitate social ties between the youth participants as well as the youth and programme staff/volunteers. Nevertheless, we found that structured leisure does not necessarily assist in the formation of relationships between street-involved youth and members of the mainstream community outside of the programme. We show how the ways the youth took up dominant discourses concerning street-involved youth and engaged with technologies of the self-influenced their social relationships and their ties to the community. These findings complicate our understanding of structured leisure's potential benefits for street-involved youth.